FUZZY CONTROL SYSTEM FOR TECHNOLOGICAL PROCESS PARAMETERS (Web of Technology: Multidimensional Research Journal, 2024)
The paper considered issues of research into a fuzzy control system for the warping process. To study the warping process its mathematical model is constructed. The process of breakage the warp of the threads under oscillation conditions in a warping machine is considered. The forces and moments that arise due to oscillations, tensions and hanging threads and the influencing effects on the sag have been studied. In the initial mode, the time constant is reduced and additive disturbances are not taken into account; the transient process is not significantly improved by using a fuzzy controller. With an increase in the time constant or when taking into account external disturbances, the presence of a fuzzy controller made it possible to improve the quality of control.